2020
DOI: 10.1186/s40035-020-00200-7
|View full text |Cite
|
Sign up to set email alerts
|

The human olfactory system in two proteinopathies: Alzheimer’s and Parkinson’s diseases

Abstract: Alzheimer’s and Parkinson’s diseases are the most prevalent neurodegenerative disorders. Their etiologies are idiopathic, and treatments are symptomatic and orientated towards cognitive or motor deficits. Neuropathologically, both are proteinopathies with pathological aggregates (plaques of amyloid-β peptide and neurofibrillary tangles of tau protein in Alzheimer’s disease, and Lewy bodies mostly composed of α-synuclein in Parkinson’s disease). These deposits appear in the nervous system in a predictable and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 196 publications
2
74
0
Order By: Relevance
“…Interestingly, α-synuclein (α-syn) aggregates (Lewy bodies and neurites) have been described in the olfactory bulb (OB) at early neuropathological stages of the disease 8,9 . In fact, these deposits are particularly conspicuous in the OB [10][11][12][13] . A previous study in our laboratory showed that Lewy bodies and Lewy neurites were present in mitral cells and the inner plexiform layer and they were particularly abundant in the anterior olfactory nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, α-synuclein (α-syn) aggregates (Lewy bodies and neurites) have been described in the olfactory bulb (OB) at early neuropathological stages of the disease 8,9 . In fact, these deposits are particularly conspicuous in the OB [10][11][12][13] . A previous study in our laboratory showed that Lewy bodies and Lewy neurites were present in mitral cells and the inner plexiform layer and they were particularly abundant in the anterior olfactory nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…N = 30,*p < 0.05 vs. the control group; #p < 0.05 vs. pre-anesthesia. in both AD and PD patients (Kubota et al, 2020;Ubeda-Bañon et al, 2020). In the previous studies on AD patients with olfactory impairment, it was found that the level of serum acetylcholine was significantly reduced, which not only affects memory function, but also plays an important role in the olfactory system, indicating that the reduction of acetylcholine may also be a cause of the olfactory impairment in AD patients (Beach et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…The other mechanism can be explained by the neurocognitive effects of OSA. Previous studies have shown that neurocognitive dysfunction leads to olfactory malfunctioning in patients with neurodegenerative diseases such as Alzheimer’s and Parkinson’s [ 21 23 ]. Similarly, patients with OSA have impaired cognitive functions as a result of sleep fragmentation, sleep loss, arousals, intermittent hypoxia, and hypoxia-reoxygenation episodes [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%